MODEL TRANSFORMASI KETERAMPILAN DUKUN JALUR DI KABUPATEN KUANTAN SINGINGI (Proceeding 7th International Seminar on Regional Education, 2015)
Abstrack The transformation model of samanâs jalur (canoe) skill in this research was moving activity or samanâs function to candidate of saman starting from the predaration of making jalur (canoe) to returning it to the jalur home magically. The main priority of this research was to know the activity, the function, and the transformation model of samanâs jalur skill in Kuantan Singingi Regency. Based on the main priority, there were 23 sub-focus as consentration. The research method used was descriptive qualitative. The location of the research was Kuantan Singingi where the jalur race tradition hasbeen developed and preserved. The data were taken from interview, and documentation. The data analysis used interpretative approach trhough social and human as text. The result of the research was 23 activities and functions of saman related to jalur/canoe race. The skill obtained by the candidate of saman was from the teacher through the transformation proceess such as direct learning, task, assingmant, and direct exercise.Keywords: transformationi, skill, saman, jalur (canoe).